A Quo Vadis Penambahan Masa Jabatan Kepala Desa Pasca Terbitnya Undang Undang No. 3 Tahun 2024 tentang Desa: Quo Vadis Penambahan Masa Jabatan Kepala Desa Pasca Terbitnya Undang Undang No. 3 Tahun 2024 tentang Desa - Ahmad Althof; Alfan Khairul Ichwan (Jurnal Hukum Lex Generalis, 2023)
This research aims to identify and reconstruct Quo Vadis regarding the increase in the term of office of village heads after the issuance of Law no. 3 of 2024 concerning Villages. The type of research used is normative juridical. The results of the study were obtained by confirming that term limits are a principle of constitutionalism to prevent abuse of power. The proposal to extend the term of office of the village head does not always mean increasing the effectiveness of performance and can affect the dynamics of democracy at the village level. Therefore, the political and legal system must be able to create a healthy and fair principle of leadership rotation. The urgency and value of extending the term of office of village heads needs to be reviewed, considering the potential negative impact on village development and democracy. Furthermore, the urgency of extending the term of office is based on the need to increase productivity and complete village development as well as reduce post-election polarization. However, negative implications such as potential authoritarianism, abuse of power, and stagnation of leadership regeneration make this proposal controversial. In addition, extending the term of office for too long can cause political boredom and decreased community participation in village democracy